Disruption of Adult Neurogenesis in the Olfactory Bulb Affects Social Interaction but not Maternal Behavior - Feierstein, Claudia E.; Lazarini, Françoise; Wagner, Sebastien; Gabellec, Marie-Madeleine; De Chaumont, Fabrice; Olivo-Marin, Jean-Christophe; Boussin, François D.; Lledo, Pierre M.; Gheusi, Gilles (Frontiers in Behavioral Neuroscience, 2010)
Adult-born neurons arrive to the olfactory bulb and integrate into the existing circuit throughout life. Despite the prevalence of this phenomenon, its functional impact is still poorly understood. Recent studies point to the importance of newly generated neurons to olfactory learning and memory. Adult neurogenesis is regulated by a variety of factors, notably by instances related to reproductive behavior, such as exposure to mating partners, pregnancy and lactation, and exposure to offspring. To study the contribution of olfactory neurogenesis to maternal behavior and social recognition, here we selectively disrupted olfactory bulb neurogenesis using focal irradiation of the subventricular zone in adult female mice. We show that reduction of olfactory neurogenesis results in an abnormal social interaction pattern with male, but not female, conspecifics; we suggest that this effect could result from inability to detect or discriminate male odors and could therefore have implications for the recognition of potential mating partners. Disruption of olfactory bulb neurogenesis, however, neither impaired maternal-related behaviors, nor did it affect the ability of mothers to discriminate their own progeny from others.